BIM-Integrated Construction Safety Risk Assessment at the Design Stage of Building Projects - Indah Suci Rahayu (Fakultas Teknik Universitas Borobudur, 2022)
The construction industry has a higher rate of work accidents than other industries. As a proactive approach to safety management, Construction Hazard Prevention through Design (CHPtD) can significantly eliminate or reduce construction safety risks. This method consists of three indices namely Likelihood, Consequence and Exposure. Likelihood and consequence index of 19 construction jobs using 2018 injury and death data. Only 4 types of work are shown in this case. The findings conclude that the index of relative mortality frequency (RFI) of roofers (47-2180) and the index of relative frequency of day-going injuries (RDAIFI) of construction workers (47-2060) are relatively high. In addition, construction equipment operators relative day-to-day injury severity (RDAIS) rates (47–2070) are 3.3 times that of roof operators (47–2180). These results validate that using plug-ins in Revit can quickly calculate the construction safety risks of various design plans in a very short time and show that the plug-ins developed have very good engineering application value.